Hoax News on the 2019 Presidential Election Campaign on Social Media - Febriyanti, Erma; Subyantoro, Subyantoro; Wagiran, Wagiran (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Technological developments have made online media a preference for delivering news. News that is spread in online media influences people's mindset and life. This has implications for the high potential for people to be trapped in fake news that is massively spread in online media. This study analyses the hoaxes in the 2019 presidential campaign. The results discuss the fake news, namely (1) 7 fake news from 35 findings of fake news with a percentage of 20%, (2) 3 findings of types of fake news (clickbait) with a percentage of 8%, (3) 4 findings of confirmation bias with a percentage of 12%, (4) 6 findings of false news types of misinformation with a percentage of 18%, (5) there are 6 findings of satire types of fake news with a percentage of 18%, (6) 3 findings of post-truth types of fake news, with a percentage of 8%, (7) there are 5 findings of fake news types propaganda with a percentage of 16%. Basically, fake news spread in online media is nothing but leading readers to certain opinions that are full of political interests.